Construction of tissue microarrays from core needle biopsies – a systematic literature review. Issue 3 (25th October 2015) - Albanghali, Mohammad; Green, Andrew; Rakha, Emad; Aleskandarany, Mohamed; Nolan, Chris; Ellis, Ian; Cheung, Kwok‐Leung
Abstract: In some clinical circumstances, core needle biopsy (CNB) may be the only source of material from cancer tissue for diagnostic use. The volume of tissue available in a CNB is low, and opportunities for research use can therefore be limited. The tissue microarray (TMA) principle, if applied to the use of CNBs, could facilitate research studies in circumstances where CNB specimens are available. However, various challenges are expected in applying such a technique in CNBs, which has limited their use in research. We therefore conducted a systematic review of the literature on this subject. A systematic search was carried out with CINAHL, EMBASE, the Cochrane library, and MEDLINE, to identify studies that have primarily developed methods for constructing TMAs from CNBs. Eight studies were found to meet the inclusion criteria; six of these employed the vertical rearrangement technique, and two used multiple layers of biopsy tissue. Representation of the CNB was significantly influenced by the quantity of tumour cells present in the original biopsy and the degree of heterogeneity of biomarker expression. This review shows that technologies have been developed to enable construction of TMAs from CNBs. However, challenges remain to improve amplification and representation.